A comparative study of extracellular enzymes from chromoblastomycosis agents reveals the potential association of phospholipase with the severity of the lesions. (October 2020) - Montoya, Alexandra M.; Montesino, Cintia Amaral; Carrión-Álvarez, Diego; González, Gloria M.; Rojas, Olga C.
Abstract: Chromoblastomycosis is a chronic, progressive subcutaneous mycosis that is endemic in tropical and subtropical countries. Cladophialophora carrionii and Fonsecaea pedrosoi are prevalent etiological agents. The potential role of the proteolytic activity of extracellular enzymes in these fungi and its relationship with the pathogenesis of the disease has not been proven. Some phenotypic traits have been associated with the virulence of other fungi; i.e., their different rate of protease, phospholipase, and esterase excretion, melanin, and thermotolerance. The aim of this study was the identification of extracellular enzymes that could be considered virulence markers of chromoblastomycosis agents. Therefore, we tested 29 C. carrionii and 11 F. pedrosoi clinical isolates to determine their hydrolytic and physiologic characteristics. All the tested isolates grew at a range of 30°–37 °C; except 2 strains of F. pedrosoi that grew slowly at 40 °C. We noticed that the hydrolytic capabilities of the tested isolates were positive for urea hydrolysis in almost all, while both strains were negative for DNase, hemolysin, and gelatin. C. carrionii and F. pedrosoi had phospholipase and esterase activity. These findings were similar for most isolates. All strains showed an association between phospholipase activity and moderate to severe lesions. However, only in F. pedrosoi isolates, the association remains significant. We conclude that the different enzymatic production reported here may be linked to the clinical manifestations of these pathologies. Notwithstanding, the influence of other virulence factors is not excluded. Highlights: Preponderant role of phospholipase in the pathogenesis of chromoblastomycosis. Phospholipase as potential virulence marker of Fonsecaea pedrosoi . Association of Fonsecaea pedrosoi with moderate and severe lesion.